Preference for Alternative Communication Modality Based on Reinforcer Quality and Availability. Issue 4 (July 2022) - Cariveau, Tom; Hunt, Katelyn; Robbins, Halley; Brown, Alexandria R.
Preference for augmentative or alternative communication (AAC) systems has received growing interest in work with individuals with developmental disabilities. An individual may choose a modality based on technological (e.g., auditory-output) or aesthetic features of a system; however, it is ideal that functional features (i.e., effectiveness in producing a reinforcer) affect preference to a much greater extent. Prior research has treated preference as a static variable and may commonly report a lack of preference for a modality or control by irrelevant features of the assessment (e.g., position of the modality in an array). The current study assessed the preference for AAC modalities of a teenager with autism spectrum disorder and intellectual disability using a concurrent-chains procedure. This study extended prior research by including additional methods to ensure accurate assessment of preference (i.e., a control condition) and a reinforcer manipulation to determine whether preference was controlled by non-functional (e.g., aesthetic) or functional (i.e., reinforcer quality and availability) variables. Preference was found to be functionally related to reinforcer availability, including when rapidly alternated between modalities. Moreover, the participant consistently allocated responding away from the control condition. Implications for self-determination and suggestions for future research on preference for AAC systems are considered.